Strategy of development of the business of the farmers group in the district of Bandung - Monika, Ajeng; Wijaya, Fanji (Institute of Computer Science (IOCS), 2024)
The objective of this study is to develop a design-oriented innovation strategy for the Potato Farmers Group through the formulation of strategies aimed at opportunity generation. This study employs a qualitative methodology with a case study approach. The researchers interviewed key informants who met the following criteria: they had to be the potato farmer group's core manager, still actively involved in the group's management, have potato farmland, and be directly involved in the cultivation of potato crops. These individuals were thought to be the most knowledgeable about the business situation of the potato farmer group. In order to create business plans that recognize various possibilities, threats, strengths, and weaknesses as crucial elements in business development, the IFE matrix design, the EFE matrix, and the QSPM matrix are utilized. The Potato Farmers Group is in cell V position and has the ability to increase market share, improve production methods, and leverage technology for marketing, according to the findings of the Internal and External Matrix (IE) assessment. Finding the appropriate strategy formula is the first step in starting a firm.